Estudo dos efeitos da hipóxia e anóxia durante o crescimento micelial de Metarhizium Robertsii na tolerância a estresses de conídios e regulação de genes - (:unkn) unknown (Universidade Brasil, 2022)
Little is known about the impact of hypoxia and anoxia during mycelial growth on tolerance to different stress conditions of fungal conidia development. Metarhizium robertsii conidia were produced on potato dextrose agar (PDA) medium under normoxic (control = normal oxygen concentrations), continuous hypoxia and transient anoxia, as well as minimal medium. The tolerance of conidia produced under these different conditions was evaluated in relation to moist heat (thermal stress), menadione (oxidative stress), potassium chloride (osmotic stress), UV radiation and 4-nitroquinoline-1-oxide (genotoxic stress 4-NQO ). Growth under hypoxic conditions induced greater tolerance of M. robertsii conidia to menadione, KCl and UV radiation. The transient anoxic condition induced greater tolerance of conidia to KCl and UV radiation. Nutritional stress (ie, minimal medium) induced greater tolerance of conidia to heat, menadione, KCl and UV radiation. The hsp30 and hsp101 gene encoding a heat shock protein was overexpressed in molecular analysis under anoxic condition. In conclusion, growth under hypoxia and anoxia produced conidia with greater stress tolerance than conidia produced under normoxic conditions. The nutritional stress generated by the minimal medium, however, induced a much higher stress tolerance. This condition also caused the highest level of gene expression in the hsp30 and hsp101 genes. Allowing concluding that there was a greater adaptation to the stress of the conidia produced under nutritional stress, hypoxia and anoxia.
Keywords: Fungos entomopatogênicos; Hipóxia; Anóxia; Estresses; Adaptação; Engenharia Biomédica (Bioengenharia)